(untitled) (Comparative & International Education Series, 2021)
The growth of internationalization in U.S. institutions has prompted university administrators to consider hiring foreign-born faculty to lead on campus. Previous studies show that despite foreign-born faculty members being more productive than their U.S. counterparts, many of them are dissatisfied with their jobs (Lee & Lim, 2017; Mamiseishvili & Rosser, 2010). This chapter provides insights on the roles and benefits of foreign-born faculty integration in breaking down barriers (e.g., culture, communication, social isolation, teaching and leadership) they experience on campus. In addition, it also discusses the roles of faculty integration with faculty growth, job satisfaction, retention, and, most importantly, campus globalization.